Bulk-fill versus layering pure ormocer posterior restorations: A randomized split-mouth clinical trial - Torres, Carlos Rg [UNESP]; Jurema, Ana Lb [UNESP]; Souza, Mauricio Yde [UNESP]; Di Nicoló, Rebeca [UNESP]; Borges, Alessandra B. [UNESP] (My University, 2021)
PURPOSE: To evaluate the clinical performance of Class II restorations made with bulk-fill or layering pure ormocer materials, as well as the time necessary to fill the preparations. METHODS: After ethics approval, a randomized controlled split-mouth clinical trial was performed. 30 subjects were selected according to the inclusion/exclusion criteria, and two restorations were randomly performed in each first or second molar that presented caries, fracture, or cosmetic needs. One restoration was done with the bulk-fill material Admira Fusion x-tra, applied with increments up to 4 mm (intervention group), while the second was performed with the regular Admira Fusion, applied by a 2 mm layering technique (control group). The universal adhesive system Futurabond U was used for both groups. The subjects and examiners were blinded, and the examiners were previously calibrated. The restorations were evaluated according to FDI criteria, after 7 days, 6, 12 and 24 months, and the outcome was success rate based on esthetic, functional and biological properties. The time necessary for application of both materials into the preparations was also measured. RESULTS: After 24 months, 26 patients attended the recall and 52 restorations were evaluated. The Fisher's statistical analysis (α= 5%) showed non-significant differences between techniques for esthetic, biological and functional properties in all evaluations (P> 0.05). After 2 years, 96% of the subjects for both groups did not show any sign of post-operative sensitivity and 100% of the teeth were vital and without secondary caries. Around 70% of the restorations received score excellent for surface luster, more than 83% for surface staining and 63% for color match. In relation to marginal adaptation and marginal staining, more than 80% for the layering material and 63% for the bulk showed excellent scores. Only three restorations of the 60 performed showed small fractures, although not affecting the esthetics or function. The time for composite application was significantly shorter for the bulk material (P= 0.0454). After 24 months of intraoral service, the restorations made with both materials presented similar and excellent clinical performance for all parameters analyzed. The bulk-fill material required significantly less chair time to apply than the layering one, simplifying and accelerating the restorative technique. CLINICAL SIGNIFICANCE: The bulk-fill ormocer-based composite was an appropriate alternative to the conventional layering material, since similar clinical performance was observed after 2 years, with the advantage of shorter chair time, due to simplified operative procedures.